Vision Perception-based Adaptive Pushing Assisted Grasping Network for Dense Clutters - Liu, Xinqi; Chai, Runqi; Wang, Shuo; Chai, Senchun; Xia, Yuanqing (Chinese Control Conference, 2024)
During the execution of a robotic grasping task, the task may fail due to the close proximity of multiple objects if grasping is the only motion primitive. Non-prehensile manipulations, such as pushing, can be used to rearrange objects and benefit grasping. Varying pushing actions with different speeds, distances, and routines may result in better performance. In this study, we propose a vision perception-based Adaptive Pushing Assisted Grasping Network (APAGN) system for generating a sequence of actions that includes grasping and adaptive pushing. APAGN can perceive the scene and then predict the locations of objects after an adaptive push, which adjusts the force and direction of pushing based on expected performance. To achieve a more efficient calculation, an Action Selector of APAGN is designed to choose the object with the highest expected outcome before making a prediction. The value of pushing actions is estimated based on how they benefit grasping, which breaks the limitation of manually designed rewards. Simulations show that APAGN might achieve higher action efficiency than baseline methods, especially in cluttered environments.